The Investigation Candidat Image, Social Media, and Candidat Knowledge on Intention to Vote and Decision to Vote Milenial Voter's Precidential Election 2024 on Samarinda City - Adella Dara Ferlita; Zainal Abidin; J. Kuleh (Budapest International Research and Critics University, 2022)
The purpose of this study was to analyze and prove the influence of the influence of Vote Intention on Voter's Behavior Decision on Millennial Voter's Presidential election 2019 in East Kalimantan. And this study uses a survey method with 200 samples scattered in three urban areas in the province of East Kalimantan (Kota Samarinda, Kota Balikpapan, Kabupaten Kutaikartanegara) with the sampling technique Accidental Sampling Method. Respondents were only interviewed once when meeting (cross section). Data from respondents (Primary Data) are then tabulated and tested using statistical methods. Data is collected using research aids (questionnaires). The results of the study after statistical tests using SEM-AMOS version 5.0 showed that the following results Candidate Image, Social Media, and Candidate Knowledge has significantly affected on Intention to Vote. Candidate Image, Social Mdia, has not significantly affected onVote Intention, Vote Intention was significantly affected Voter's Behavior Decision on Millennial Voter's Presidential election 2024 in Samarinda City